Perancangan Sistem Panel Surya Terkendali Dalam Dua Sumbu Untuk Peningkatan Efisiensi Pembangkitan Energi Listrik - Porman Pangaribuan; Erwin Susanto; Rinaldi Aditya Pratama (Jurnal Rekayasa Elektrika, 2019)
The use of solar panels to get electrical energy from solar energy is one effort to utilize renewable energy resources. Solar panels (solar cells) are instruments that can convert the energy of sunlight into electrical energy. Solar panels are not only used in homes or in certain places, but also in large transport equipment such as cars and on ships. Solar panels are mostly installed in a stationary or static position. Whereas the direction of sunlight will change its angle relative to the surface of the solar panel. The change is increasingly irregular if the vehicle where the panel is located moves in the direction you want to go. Conditions like this cause the absorption of solar energy by solar panels to be less than optimal. In this research, a system has been designed where the solar panel was always controlled so that the direction of sunlight always falls perpendicular to the surface of the solar panel even though it was in a changing location and the direction of the sun's light on the earth's surface was always changing. Solar panels that can maneuver in two axes of motion were controlled by a microcontroller and two servo motors as actuators to adjust the position of the solar panel so that the surface was always perpendicular (following) the direction of sunlight. From the results of the tests, it turns out that solar panels in this research design can produce power 6.51% greater compared to static solar panels output.